2010
DOI: 10.1094/phyto-100-4-0328
|View full text |Cite
|
Sign up to set email alerts
|

Population Genetic Analyses of Fusarium asiaticum Populations from Barley Suggest a Recent Shift Favoring 3ADON Producers in Southern China

Abstract: Fusarium asiaticum is the predominant causal agent of Fusarium head blight (FHB) in southern China. The genetic diversity was assessed by analyzing 448 single-spore F. asiaticum isolates from 18 sampling sites that were 10 to 2,000 km apart, using seven highly informative variable number of tandem repeat (VNTR) markers. This analysis showed a significant degree of population subdivision (P < 0.001) among populations from upper, middle, and lower valleys of the Yangtze River, with little gene flow (Nm = 1.210).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
76
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(88 citation statements)
references
References 39 publications
10
76
1
1
Order By: Relevance
“…A significant longitudinal cline in trichothecene chemotype frequencies in Canada was attributed to the recent introduction and spread of a novel, and potentially more vigorous, F. graminearum population with a 3-ADON chemotype . A very similar situation was described for F. asiaticum populations differing in trichothecene type in China (Zhang et al 2010(Zhang et al , 2012. Recent introductions may also account for regional differences in trichothecene chemotype composition reported in Louisiana and Uruguay, although regional differences in host composition were suggested as a major factor Umpiérrez-Failache et al 2013).…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…A significant longitudinal cline in trichothecene chemotype frequencies in Canada was attributed to the recent introduction and spread of a novel, and potentially more vigorous, F. graminearum population with a 3-ADON chemotype . A very similar situation was described for F. asiaticum populations differing in trichothecene type in China (Zhang et al 2010(Zhang et al , 2012. Recent introductions may also account for regional differences in trichothecene chemotype composition reported in Louisiana and Uruguay, although regional differences in host composition were suggested as a major factor Umpiérrez-Failache et al 2013).…”
Section: Discussionsupporting
confidence: 65%
“…The origin of this population structure is unclear, but may have resulted from the introduction and spread of a novel population prior to our sampling. Similar conclusions were drawn from the observation o f w i d es p r e a d c o -o cc u r r e n c e o f d i v e rge n t F. graminearum populations in North America Ward et al 2008) and from the observed population structure within F. asiaticum in China (Zhang et al 2010(Zhang et al , 2012.…”
supporting
confidence: 77%
See 1 more Smart Citation
“…The biogeographic structure exhibited by the four species within this subclade suggests that they may have evolved allopatrically within Asia. While F. asiaticum has been reported to be more prevalent in southern regions of China and Japan (Gale et al, 2002;Qu et al, 2007;Suga et al, 2008;Yang et al, 2008;Zhang et al, 2010), F. ussurianum is currently only known for the Far East of Russia, and F. vorosii appears to be largely restricted to the Far East of Russia and Hokkaido, Japan (Starkey et al, 2007;Yli-Mattila et al, 2009), although the first isolate of the latter species was initially discovered in Hungary (Tóth et al, 2005). Assessing whether F. nepalense is endemic to Nepal will require additional sampling to identify its phylogeographic distribution.…”
Section: F Nepalensementioning
confidence: 99%
“…It was the purpose of this study to characterize a F. graminearum strain collection isolated between 1969 and 2009 for its (in)sensitivity towards trifloxystrobin and to provide evidence for either acquired or natural resistance. Moreover, given the recent observations of a shift of the F. graminearum chemotype composition in different agricultural conditions (Ward et al 2008;Gale et al 2007;Zhang et al 2010) it could be hypothesized that a selective pressure caused by the increased use of fungicides might have favoured a certain chemotype. Because it has been noted that oxidative stress is triggered by fungicides and that chemotypes respond differently to oxidative stress (Ponts et al 2009), we also tested if the level of sensitivity to strobilurins differed among chemotypes.…”
Section: Introductionmentioning
confidence: 99%